Study of risk factors of cerebral strokes according to the data of regional registers and national services of medical statistics - Ognev, Victor Andreevich; Mishchenko, Marina Mikhailovna; Mishchenko, Alexander Nikolaevich; Shevchenko, Alexander Sergeevich (CPN Publishing Group, 2020)
Using the registers of patients with cerebral stroke, the frequency of occurrence of risk factors in various populations was studied. A comparison of the averaged data was carried out, followed by a comparison with the data of national and international prospective studies of stroke risk factors. The main (“significant”) risk factors remain unchanged in any population. Their corrections are attributed to 2/3 of the success in reducing mortality from strokes (1/3 refers to the success of therapy).

С помощью регистров больных церебральным инсультом изучена частота встречаемости факторов риска в различных популяциях. Проведено сравнение усредненных данных с последующим сравнением с данными национальных и международных проспективных исследований факторов риска инсульта. Основные («значимые») факторы риска остаются неизменными в любой популяции. Их коррекции приписывают 2/3 успеха снижения смертности от инсультов (1/3 относится к успехам терапии).
Изучение факторов риска церебральных инсультов по данных региональных регистров и национальных служб медицинской статистики
Keywords: cardiovascular diseases; cerebral stroke; risk factors; registers of stroke patients; epidemiological studies; state medical statistics; сердечно-сосудистые заболевания; церебральный инсульт; факторы риска; регистры больных инсультами; эпидемиологические исследования; государственная медицинская статистика